Exploring the Intersections of Trauma, Structural Adversity, and Psychosis among a Primarily African-American Sample: A Mixed-Methods Analysis - Rosen, Cherise; Jones, Nev; Longden, Eleanor; Chase, Kayla A.; Shattell, Mona; Melbourne, Jennifer K.; Keedy, Sarah K.; Sharma, Rajiv P. (Frontiers in Psychiatry, 2017)
Traumatic life events (TLEs) have been associated with multiple psychiatric diagnoses, including anxiety disorders, major depression, PTSD and psychosis. In order to advance our understanding of the complex interactions between forms of adversity as they manifest across the lifespan, psychosis, and symptom content, we undertook a mixed methods investigation of TLEs and psychosis. Our research explored the association between cumulative exposures, type of TLE, and proximity to the traumatic event and psychosis; the association between TLEs and clinical symptomology including specific types of delusions and/or hallucinations; and how qualitative data further inform understanding of complex relationships and patterns of past trauma and symptoms as they unfold over time. There were a total of 97 participants in the quantitative study sample, 51 participants with present state psychosis and 46 non-clinical. There were a total of 34 qualitative study participants, all of whom were experiencing psychosis. The quantitative analysis showed that when comparing persons with psychosis to the non-clinical group there were no group differences in the overall total score of TLEs. However, there was a significant difference in cumulative TLEs that “Happened” demonstrating that as the number of TLEs increased, the likelihood of clinical psychosis also increased. We also found a correlation between lifetime cumulative TLEs that “Happened” and PANSS 5-factor analysis Positive, Excitement, Depression, Thought Disorder, Activation, and Paranoia scores. The qualitative analysis further built on these finding by providing rich narratives regarding the timing of trauma related onset, relationships between trauma and both trauma-related and religious-spiritual content, and trauma and hallucinatory modality. Analysis of participant narratives suggests the central role of localized cultural and sociopolitical influences on onset, phenomenology and coping and contributes to a growing literature calling for strengths-based, client-driven approaches to working with distressing voices and beliefs that centers the exploration of the personal and social meaning of such experiences including links to life narratives. Findings also underscore the clinical importance of trauma assessment and trauma-informed care.